PHYSICOCHEMICAL AND FUNCTIONAL PROPERTIES OF DIETARY FIBER FROM BAMBOO SHOOTS (PHYLLOSTACHYS PRAECOX) - Wang, Cai-Hong; Ma, Yi-Long; Zhu, Dan-Ye; Wang, Hao; Ren, Ya-Fei; Zhang, Jian-Guo; Thakur, Kiran; Wei, Zhao-Jun (Emirates Journal of Food and Agriculture, 2017)
Dietary fiber are non-digestible constituents of plant cell walls, and comprise a necessary component of diet and its positive connection with human health. Till now, there is no report about the extraction and physicochemical and functional properties of dietary fiber from bamboo shoots. To find the potential applications of dietary fiber from bamboo shoots in food and health products, the effects of chemical, enzymatic methods and particle size distribution on the chemical and structural composition, physicochemical, and functional properties of dietary fibers (DFs) from bamboo shoots were studied. The results showed that BSEDF and BSCDF had higher total DF and higher soluble DF, respectively. The crystalline regions calculated to be higher in latter and both had irregular surfaces and diverse monosaccharide composition. Both fibers showed good functional properties [water retention capacity (WRC) (11.24-15.13g/g), water swelling capacity (WSC) (18.84-28.75 mL/g), oil holding capacity (OAC) (6.71-10.15 g/g), glucose adsorption capacity (GAC) (0.08-6.89 mmol/g) and glucose retardation index (GRI) (3.57-40.92%)]. WRC of BSCDF and BSEDF decreased with the increase in the mesh size (40-200) while, WSC and OAC increased with mesh sizes (40 to 120), followed by decrease above mesh120. Both particle size and extraction methods significantly affected GRI. In conclusion, physico-chemical properties of fibers can be manipulated through treatments (chemical and enzymatic) to improve their overall functionality. Therefore, both BSCDF and BSEDF can find potential applications in food and health products as a functional ingredient in different aspects.